2021
DOI: 10.3389/fmars.2021.721626
|View full text |Cite
|
Sign up to set email alerts
|

Fleshy Red Algae Mats Influence Their Environment in the Mediterranean Sea

Abstract: In the Mediterranean Sea, the fleshy red alga Phyllophora crispa forms dense mats of up to 15 cm thickness, mainly located on rocky substrates in water depths below 20 m. Because of the observed density of these mats and some first observations, we hypothesize that P. crispa is a yet undescribed ecosystem engineer that provides a multitude of ecological niches for associated organisms along small-scale environmental gradients. Therefore, we conducted an in-situ pilot study in the Western Mediterranean Sea to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 95 publications
2
2
0
Order By: Relevance
“…High abundances of erect and branching colonies (e.g., C. pyriformis, Scrupocellaria sp., Crisia sp.) on P. crispa and P. oceanica shoots are likely related to water current gradients inside P. crispa mats [46], as demonstrated before for P. oceanica meadows [47][48][49]. This is further supported by an experimental study that has confirmed negative phototaxis for the larvae of some erect bryozoan species [50], since strong light gradients are present in both habitats [46].…”
Section: Differences In Bryozoan Abundances and Diversity Between Phy...supporting
confidence: 75%
See 2 more Smart Citations
“…High abundances of erect and branching colonies (e.g., C. pyriformis, Scrupocellaria sp., Crisia sp.) on P. crispa and P. oceanica shoots are likely related to water current gradients inside P. crispa mats [46], as demonstrated before for P. oceanica meadows [47][48][49]. This is further supported by an experimental study that has confirmed negative phototaxis for the larvae of some erect bryozoan species [50], since strong light gradients are present in both habitats [46].…”
Section: Differences In Bryozoan Abundances and Diversity Between Phy...supporting
confidence: 75%
“…While the leaves of P. oceanica mainly host encrusting forms, P. crispa hosted additional growth types (petraliform and creeping), further underlining the structural diversity of the bryozoan community. As demonstrated above for P. oceanica meadows, this structural diversity is likely linked to gradients in water currents and light intensity, which have recently been confirmed for P. crispa mats [46].…”
Section: Differences In Bryozoan Abundances and Diversity Between Phy...supporting
confidence: 66%
See 1 more Smart Citation
“…Thus, these deep water observations in Kongsfjorden are of special significance and may have an overlooked ecological importance. Schmidt et al (2021) hypothesize that deep water foliose red algae mats in the Mediterranean Sea are a yet undescribed ecosystem engineer that provides a multitude of ecological niches. If we consider that Phycodrys becomes up to 4 years old, a tetrasporophyte may release up to 550,000 tetraspores or female gametophytes up to 120,000 carpospores per individual (Schoschina 1996) and houses up to 7583 individuals of epifaunal species per 100 g fresh weight (Lippert et al 2001), the role of deep water foliose red algae for the Arctic food web and macroalgal carbon cycling might be considerable, but remains unknown.…”
Section: Macroalgal Distribution Along the Depth Gradient And Fjord Axismentioning
confidence: 99%